Beyond 'what works': implementing sex offender treatment programs in the 'real world'. Issue 3 (3rd April 2022) - Rayment-McHugh, Susan; Belton, Emma; McKillop, Nadine; Christensen, Larissa S.; Prenzler, Tim; Hine, Lorelei
Abstract: Extending the 'what works' tradition in correctional research, realist evaluation approaches champion the need to understand the nuances of program implementation and effectiveness, asking "what works, for whom, in what circumstances, in what respects, and how?". This highlights the importance of understanding how programs work in 'real world' settings, and not simply whether or not they produce a positive outcome overall. Informed by this approach, the current study employed focus groups and interviews with corrective services programs staff in Australia, to explore factors that impact program success and key program implementation considerations. Findings reveal system-, program-, and individual- level factors that appear to impact program success, largely by constraining program delivery. Identified implementation considerations included program design and delivery, and staffing and resources. By examining the nuances of program delivery, this study provides a better understanding of the 'real-world' operation of custodial sex offender treatment programs, and adds important context to reported outcome studies.